CONTENT AND METHODS OF DEVELOPING STUDENTS' PHYSICAL-TECHNICAL ABILITIES IN PHYSICS TEACHING - Dilsuz Omonovna Astanova (Bright Mind Publishing, 2025)
This article addresses the issues of developing students' physical and technical abilities in teaching physics at secondary schools. The study experimentally examined the effectiveness of interactive methods, laboratory activities, and collaborative work forms. The results confirm that interactive and practical approaches significantly enhance students' analytical thinking and practical skills. The conclusions of the study include recommendations for further improvement and wider implementation of pedagogical technologies.
Keywords: Physical-technical abilities, interactive methods, laboratory activities, collaborative work forms, pedagogical technologies.